Pemanfaatan Abu Boiler Kelapa Sawit terhadap Pertumbuhan Tajuk Tanaman Tomat - Nurul Hidayati; Asro Laelani Indrayanti (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2015)
The purpose of this research is gaining influence boiler ash on growth and yield of tomatoes, (4) obtain optimal dosing of boiler ash is curuently applied to some media. This research was conducted at Jl. Manjuhan Palangkaraya. The time of this study will last for 4 months This study uses a completely randomized design factorial 2 factors. The first factor is the dose Abu boiler with a 5 stage treotment (without ash, 5 ton.ha-1, l0 ton ha-1, 15 ton.ha-1 and 20 ton.ha-1 . The second factor is the type of media with 3 levels of treatment (Soil sand, soil Podsolid and Peat. The treatment combinotion obtained as-mony as 15 combinations of treatment, with a repeat 3 times. The survey results reveoled that (1) the interaction of growth media and boiler ash dose showed significantly different results against 2,4 dan 6-wieks after planting variables plant height, amount of leaves on the age, 2, 4 and 6 weeks after, plantig, stem diameter at 4 weeks afier planting, and shoot dry weight lastest research. Treatment combination boiler ash 15 ton / ha and peat media (treatment b4t3) provide significant variahles plant height, leaf amount, diameter of stock, and shoot dry weight.